KUALITAS SEMEN BEKU DOMBA GARUT (Ovis aries) PENAMBAHAN SUKROSA DALAM PENGENCER SEMEN KUNING - Herdis suharman (BERITA BIOLOGI, 2017)
The objective of this research was to examine the effect of sucrose in improving the quality of the plasma membrane intact and sperm motility of frozen semen of Garut ram. Semen was collected using artificial vagina weekly from six mature garut rams.   Immediately after initial evaluation, fresh semen was divided into four parts and diluted with Tr s extender without sucrose (T0), Tris extender + sucrose 0.2g/100 ml (T1), Tris extender + sucrose 0.4g/100 ml (T2) and Tris extender + sucrose 0.6g/100 ml (T3), respectively.  Results of this research showed that the percentage of sperm motility after thawing in T2 (49.00 ± 5.48%)  was significantly (P<0.05) higher than T0 (42.00 ± 2.74%) but was not significantly difference (P>0.05) than T1 (46.00 ± 4.18%)and T3 (48.00 ± 4.47%).   Evaluation of plasma membrane intact showed that T1 (62.33 ± 6.51%) was s gnificantly different (P <0.05) w h T0 (49.40 ± 2.19%) but was not significantly different (P> 0.05) than T2 (58.50 ± 4.97%) and T3 (56.40 ± 5.90%).  In conclusion, he addition of sucrose in semen extender  improved the quality of frozen semen of Garut ram.  Concentration of 0.2g / 100 ml is the op ma dose to improve the quality of the plasma membrane intact and motility of spermatozoa during the freezing process.